Pengaruh Latihan Small Sided Games Terhadap Ketepatan Short Pass Kaki Bagian Dalam Pada Pemain Rajawali Football Club U-14 Kota Semarang 2023 - Noor Ahmad; Tri Nurharsono; Martin Sudarmono (Universitas Negeri Semarang, 2024)
This research based on insufficient quality passing especially short pass of the legs in when their every move is passing the basic technique u-14 poor passing.This study attempts to find out the accuracy of passing from the small sided games improve the quality of the legs in the short pass u-14 eagle fc.The results of the study with this t ( paired t ) tests show the short pass of the legs in having the significance of t count ( 2-tailed ) & gt; t table ( 1,79 & gt; 1,67 ) hypothesis accepted.A small sided games can improve the accuracy of short pass of the legs in.While in short pass of the legs in football also have significant value of t count ( 2-tailed ) & gt; t table ( 25,59 & gt; 1,69 ) received the hypothesis.A small sided games will increase the quality of passing football player player u-14 rawajawali semarang city fc.